Toward integrative genomics study of genetic resistance to Salmonella and Campylobacter intestinal colonization in fowl - Calenge, Fanny; Beaumont, Catherine (Frontiers in Genetics, 2012)
Salmonella enterica serotypes Enteritidis and Typhimurium and Campylobacter jejuni are responsible for most cases of food poisoning in Europe. These bacteria do not cause severe disease symptoms in chicken, but they are easily propagated by symptomless chicken carriers which cannot be easily isolated. This animal tolerance is detrimental to food safety. In this particular case, increasing animal’s resistance is not sufficient, since some animals considered as resistant are able to carry bacteria during several weeks without displaying disease symptoms. We review studies aimed at evaluating the resistance of chicken to Salmonella and Campylobacter intestinal colonisation, either a few days or several weeks after infection. While studies of the genetic control of Campylobacter colonisation are only beginning, mostly due to technical difficulties in infection protocols, genetic studies of Salmonella colonisation have been conducted for now more than twenty years. They have initially reported an estimation of the genetic parameters associated with resistance to Salmonella colonisation and are now aimed at identifying the genomic regions controlling variation of this trait in experimental lines and commercial populations. With the advent of high-throughput genomics, we are closer than ever to identify the true genes controlling resistance to Enterobacteria colonisation in chicken. The comparison of genes involved in early resistance to intestinal colonisation with genes controlling resistance to bacteria persistence several weeks after infection (i.e. carrier-state) should soon highlight the differences between the molecular mechanisms underlying those two distinct phenotypes. It will also be highly interesting to compare the genes or genomic regions controlling Campylobacter and Salmonella, in order to evaluate the feasibility of a selection conducted on both bacteria simultaneously.